Ben Bernanke in Doha: The effect of monetary policy on optimal tariffs - Wolfgang Lechthaler (Kiel Institute for the World Economy (IfW), 2016)
Trade liberalization can imply slow and long adjustment processes. Taking account of these adjustment processes can change the evaluation of trade policy, especially when policy makers care more about the next couple of years than the infinite future. In this paper I analyze the setting of tariffs in a two-country model taking account of adjustment processes with special emphasis on the effects of nominal price rigidity and monetary policy. I show that nominal price rigidity induces policy makers with a short planning horizon to set lower tariffs because it enhances the short run boom following a cut in tariffs. Monetary policy that aggressively fights deviations from its inflation target leads to even lower tariffs.
Keywords: E52; F11; F12; F13; 330; tariffs; dynamic trade model; monetary policy